Social Media's Impact on Language Evolution: Analysing Posts from Facebook, Twitter, and Whatsapp Users - Nghipondoka, Tertisia Ndina; Neshila, Faustina Kashinauua; Shivute, Johannes (International Journal of Linguistics and Translation Studies, 2025)
This research investigates the interplay between social media and language evolution, focusing on the linguistic innovations observed in posts by Namibian users across prominent platforms such as Facebook, WhatsApp, and Twitter. Employing a qualitative research approach, the study aims to uncover linguistic innovation by examining the strategies employed and motivations driving language evolution within this digital landscape. Through the analysis of fifty selected conversations using Discourse Analysis, the study reveals a distinctive pattern of informal structures prevalent among Namibian youth, deviating from the conventions of standard English. These linguistic innovations include the use of emojis and emoticons, code-switching, colloquialisms and slang, vulgar language and acronyms. The research concludes that the choice of linguistic innovation strategies is influenced by platform-specific features, such as text limits and the visibility of conversations or posts. The findings reveal that linguistic creativity on social media is not a departure from established norms but an evolution that reflects the rich diversity of global English varieties. This research contributes to an understanding of the relationship between social media, linguistic innovation, and the cultural context within which language evolves.